Risk management for Islamic banks - Salem, Rania Abdelfattah (Edinburgh guides to Islamic finance., 2013)
This guide provides an integrated, structured process for managing risks in Islamic banks. It includes risk identification, measurement and mitigation, and compares risk management in conventional and Islamic banks. Using simulated Islamic bank financial statements, it demonstrates the integrated risk management process, and investigates how risk regulatory insights have implications for banking policy.